2014
DOI: 10.1097/scs.0000000000000944
|View full text |Cite
|
Sign up to set email alerts
|

Quick and Accurate Measures in Negative Pressure Pulmonary Edema

Abstract: Perioperative pulmonary edema is a rare complication of maxillofacial surgery. However, this potentially fatal complication may arise during any maxillofacial surgery. Negative pressure pulmonary edema can be caused by upper airway obstruction after operation. When this phenomenon arises, if not treated properly, it progresses rapidly causing fatal outcomes. Because orthognathic surgery is performed mostly on healthy and young patients, surgeons and anesthesiologists might neglect the possibility of such compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
1
9
0
1
Order By: Relevance
“…Krodel et al [5] reported that a 25-year-old man showed the symptoms of pulmonary edema within first hour after surgery without specific time window. Hong et al [6] reported the case that began to present pink frothy sputum soon after clear consciousness. Here, our patients rarely presented pink frothy sputum after reversing the upper airway obstruction-induced dyspnea, she stayed conscious and the time window was over 30 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krodel et al [5] reported that a 25-year-old man showed the symptoms of pulmonary edema within first hour after surgery without specific time window. Hong et al [6] reported the case that began to present pink frothy sputum soon after clear consciousness. Here, our patients rarely presented pink frothy sputum after reversing the upper airway obstruction-induced dyspnea, she stayed conscious and the time window was over 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…Other procedure that increases the risk of NPPE includes oropharyngeal, head, and neck surgery. Five [812] of the reported 29 cases involved upper respiratory tract surgery, and 10 [1,3,6,7,1318] of the cases involved head and neck surgery, which may be related to tissue swelling and the sensitive dilator muscle of the upper airway in head and neck surgeries. Although our patient underwent endoscopic thyroidectomy with no wound in the neck skin, it was inevitable for neck tissue and muscle injury.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 69 studies, all of which were case series or case reports met final inclusion criteria (Supplemental Table 2). 2,3,973 Studies were dated between 1977 and 2016. In total, data from 87 individual patients was accessed across 69 studies.…”
Section: Resultsmentioning
confidence: 99%
“…There are very limited case reports which present NPPE associated with dental procedures and orofacial surgery in the literature [3,[5][6][7][8][9][10]. This report aims to present the case that had NPPE after bimaxillary orthognathic surgeries and to review the reported data related to NPPE after oral procedures.…”
Section: Introductionmentioning
confidence: 99%